Translation Strategies of Cultural-specific Items in Translating Subtitles Indonesian Documentary “Perempuan Tana Humba” - Halim, Vallen Mutiara; Nitsa, Angelique; Ayuretno, Annisa; Santoso, Wulandari (SALEE: Study of Applied Linguistics and English Education, 2024)
Translating Cultural-Specific Items (CSIs) could present numerous challenges for translators because each culture communicates differently. Experts have given some approaches to the issue of translating culturally distinctive objects. The researchers used Aixela's (1996) theory for translation technique and Newmark's (1998) theory for analysis and categorization in relation to CSI. The purpose of this qualitative study is to analyze the translation strategies used for cultural-specific items in the translation of the Indonesian documentary "Perempuan Tana Humba" by Lasja F. Susatyo and Mandy Marahimin. The researcher utilized thematic analysis to analyze the CSIs occurring in the documentary. The research concluded that out of five types of CSI proposed by Newmark, only three types of CSIs were found: material culture, social organization, and social culture. In addition, the most frequently used strategy was repetition. This study also showed that the translation strategy for the CSI was determined by the translator's concerns or considerations, such as the occasions in which the translators applied different strategies when the previously mentioned CSIs appeared again in different point of the documentary. It was noticed that various timestamps led to different translation techniques. The study is significant for the practice of translation. The research's findings, which categorize and identify the translation procedures used to translate the CSIs, may be taken into account by translation researchers as well as by present and future translators. Additionally, this study might help to clarify how to use translation procedures and what kinds of CSIs to translate for documentaries.